Making “cold” tumors “hot”- radiotherapy remodels the tumor immune microenvironment of pancreatic cancer to benefit from immunotherapy: a case report - Tong, Fan; Sun, Yi; Zhu, Yahui; Sha, Huizi; Ni, Jiayao; Qi, Liang; Gu, Qing; Zhu, Chan; Xi, Wenjing; Liu, Baorui; Kong, Weiwei; Du, Juan (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors have limited efficacy in metastatic pancreatic cancer due to the complex tumor immune microenvironment (TIME). Studies have shown that radiotherapy can cause cell lesions to release tumor antigens and then take part in the remodeling of the tumor environment and the induction of ectopic effects via regional and systemic immunoregulation. Here, we reported a case of advanced metastatic pancreatic cancer treated with immunotherapy combined with chemotherapy and radiotherapy and a sharp shift of the TIME from T3 to T2 was also observed. One hepatic metastasis within the planning target volume (PTV) was evaluated complete response (CR), the other one was evaluated partial response (PR) and 2 hepatic metastases outside the PTV were surprisingly considered PR. In the study, we found that immunotherapy combined with chemotherapy and radiotherapy achieved significant therapeutic benefits, which may provide a new strategy for the treatment of advanced pancreatic cancer.